Legal Protection for Customers in Artificial Intelligence-Based Digital Financing through the Strengthening of Banking Prudential Principles in Indonesia - Aliyah Pratiwi Hatta Aliyah Pratiwi; Subekti; Muhammad Yustina Ariwibawa; Vallencia Nandya Paramitha (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study analyzes customer protection in artificial intelligence based digital financing in Indonesia through the strengthening of banking prudential principles. Using normative legal research with doctrinal and conceptual approaches, this study examines banking, consumer protection, data protection, digital finance, and alternative credit scoring regulations. The findings show that customer protection has been recognized, but remains fragmented across several legal regimes. This condition weakens preventive protection against opaque scoring, inaccurate profiling, excessive data use, and limited remedies for automated decisions. The study proposes algorithmic prudence as a framework that integrates data governance, model validation, explainability, human oversight, and third party accountability into prudential banking obligations.